2007
DOI: 10.4049/jimmunol.178.7.4267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Placenta Growth Factor in Mice Alters Uterine NK Cells

Abstract: Placenta growth factor (PlGF; formerly PGF), a vascular endothelial growth factor gene family member, is expressed in human implantation sites by maternal uterine NK (uNK) and fetal trophoblast cells. Lower than normal concentrations of blood and urinary PlGF have been associated with impending onset of pre-eclampsia, a hypertensive disease of late human gestation characterized by limited intravascular trophoblast invasion. In pregnant rodents, delivery of the PlGF antagonist sFlt-1 or S-endoglin induces pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 42 publications
4
88
2
1
Order By: Relevance
“…However, high sFLT1 levels in the placenta likely neutralize local PlGF (Kendall et al 1996;Cindrova-Davies et al 2011;Furuya et al 2011). PlGF also regulates the maturation of uterine natural killer cells in the endometrium needed for trophoblast invasion (Tayade et al 2007). Overall, although PlGF is expressed in development, its role is largely redundant.…”
Section: Plgf Redundant In Development and Healthmentioning
confidence: 99%
“…However, high sFLT1 levels in the placenta likely neutralize local PlGF (Kendall et al 1996;Cindrova-Davies et al 2011;Furuya et al 2011). PlGF also regulates the maturation of uterine natural killer cells in the endometrium needed for trophoblast invasion (Tayade et al 2007). Overall, although PlGF is expressed in development, its role is largely redundant.…”
Section: Plgf Redundant In Development and Healthmentioning
confidence: 99%
“…Mouse uNK cells promote uterine lumen closure, angiogenesis, the rate of early fetal development and they initiate spiral artery remodelling. [13][14][15] In contrast to human uNK cells, mouse uNK cells appear in the uterus after implantation rather than following the menstrual cycle surge luteinizing hormone. 16,17 Although mouse trophoblast cells express MHC molecules, 18 mouse uNK cells may have only an indirect influence on trophoblast invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent production of PlGF by trophoblast and the presence of Flt-1 receptors on trophoblast suggest that PlGF may act in an autocrine manner to modulate the trophoblast differentiation [23]. The uNK cells can also produce PlGF [3,4,24,25], suggesting that uNK cells may support the differentiation of endothelial cells together with VEGF. The present study also showed that PlGF protein did not change under diabetes condition, although PlGF mRNA expression was decreased.…”
mentioning
confidence: 99%
“…For quantification of PlGF expression, the SYBR Green PCR Master Mix (Applied Biosystems, U.S.A.) was used. PlGF primers are designed as forward (5'-TGCTGGTCATGAAGCTGTTC-3') and reverse (5'-GGACACAGGACGGACTGAAT-3') [24]. Data were quantified using StepOne Software for StepOne and StepOnePlus Real-Time PCR system (Applied Biosystem, U.S.A.).…”
mentioning
confidence: 99%